THU0131 Tofacitinib (CP-690, 550), an oral janus kinase inhibitor: Analysis of malignancies across the rheumatoid arthritis clinical programme. (23rd January 2014) - Mariette, X.; Curtis, J.R.; Lee, E.B.; Riese, R.; Kaplan, I.; Chew, R.; Geier, J.; Wang, L.; Bradley, J.D.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor that is being investigated as a targeted immunomodulator and disease-modifying therapy for rheumatoid arthritis (RA). Objectives: To evaluate the malignancies that occurred in the tofacitinib RA programme from the Phase (P) 2, 3, and long-term extension (LTE) studies up to 29 March 2011. Methods: Data were pooled from 6 randomized P2, 5 randomized P3 studies and 2 open-label LTE studies. Patients (pts) in P3 and LTE studies were treated with tofacitinib 5 or 10 mg twice daily. Analyses included malignancy data from 1608 pts in P2, 3315 pts in P3, and 3227 pts in LTE studies (LTE pts rolled over from the P2 and P3 studies). Results: A total of 4789 patients (5651 pt-yr) received tofacitinib in the P2, P3 and LTE studies. Fifty pts receiving tofacitinib (all doses) reported malignancies (excluding non-melanoma skin cancer [NMSC]); the most common were lung (12 cases) and breast cancer (9 cases). There were 3 lymphoma cases. The overall incidence rate (IR, events per 100 pt-yr) for all malignancies (excluding NMSC) was 0.89 (95% confidence interval [CI]: 0.67, 1.17). The IRs (95% CI) of all malignancies (excluding NMSC) broken down into 0-6, 6-12, 12-18, 18-24 and >24 months based on exposure to study drug were 0.75 (0.46, 1.23), 0.73 (0.41, 1.28), 0.97 (0.48, 1.94), 1.28 (0.53, 3.08), and 1.37 (0.71, 2.63), respectively. The number of cases in each time interval was small, with resultant wide CIs. The standardised incidence ratio (SIR) (95% CI) (as compared with the Surveillance Epidemiology and End Result database covering the general population) for all malignancies (excluding NMSC), lung, breast cancer and lymphomas in the tofacitinib group were 1.11 (0.82-1.47), 2.16 (1.12, 3.77), 0.82 (0.38, 1.56) and 1.74 (0.36, 5.10), respectively. Twenty-one pts experienced NMSCs, for an IR of 0.37 (95% CI: 0.24, 0.57). By comparison, the IR of NMSC in patients treated with anti-TNF was 0.47 (0.37-0.59) in a meta-analysis of randomized controlled trials and ranged from 0.23 to 0.35 in a meta-analysis of registries. 1, 2 Conclusions: The malignancies that occurred in the tofacitinib RA programme are consistent with the type and distribution of malignancies expected for patients with moderate to severe RA. The IRs for all malignancies (excluding NMSC), lung cancer, breast cancer and lymphomas are consistent with published estimates in RA patients treated with biologic and non-biologic DMARDs. 3-6 Longer follow-up is necessary to further evaluate the potential risk of malignancies in the CP RA programme. References: Askling J, et al. Pharmacoepidemiol Drug Saf 2011;20:119-30. Mariette X, et al. Ann Rheum Dis 2011;70:1895-904. Carmona L, et al. Semin Arthritis Rheum 2011;41:71-80. Pallavicini FB, et al. Autoimmun Rev 2010;9:175-80. Simon TA, et al. Ann Rheum Dis 2009;68:1819-26. Wolfe F, Michaud K. Arthritis Rheum 2007;56:2886-95. Disclosure of Interest: X. Mariette Consultant for: Pfizer Inc, J. Curtis Grant/Research support from: Pfizer Inc, Consultant for: Pfizer Inc, E. Lee Consultant for: Pfizer Inc, R. Riese Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, I. Kaplan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Chew Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Geier Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc